Comparison of the pediatric hospitalizations due to COVID‐19 and H1N1pdm09 virus infections during the pandemic period. Issue 5 (25th January 2022) - Devrim, İlker and Böncüoğlu, Elif and Kıymet, Elif and Şahinkaya, Şahika and Çelebi, Miray Yılmaz and Cem, Ela and Düzgöl, Mine and Arıkan, Kamile Ötiken and Kara, Aybüke Akaslan and Devrim, Fatma and Ağın, Hasan and Bayram, Nuri
Abstract: There are two major pandemics in the new millennium, including the pandemic of swine influenza and the COVID‐19 pandemic. These two pandemics affected children as well as the adult population. In this case‐control study, we compared children with COVID‐19 infection and those with H1N1pdm09 virus infection. We also compared the demographic factors, underlying disease, and the requirement for intensive care admission between the hospitalized children with COVID‐19 infection and children with H1N1pdm09 virus infection who were hospitalized during the 2009 H1N1 pandemic. In this study, we evaluated 103 patients with H1N1pdm09 virus infection and 392 patients with COVID‐19 infection. The age was significantly higher in the COVID‐19 patients' group compared to the pandemic influenza group ( p < 0.001). The ratio of the children ≥12 years was 10.7% ( n = 11) in the H1N1pdm09 virus infection and 36.2% ( n = 142) in the COVID‐19 group. The rate of underlying disease was significantly higher in the patients with H1N1pdm09 virus infections ( p = 0.02). The prevalence of underlying disease in patients requiring PICU hospitalization was 69.2% ( n = 9/13) compared to 25.7% ( n = 124/482) in patients who did not require PICU hospitalization. The rate of underlying disease was significantly higher in the PICU group regardless of COVID‐19 or H1N1pdm09 virus ( p = 0.002). Our results suggest that older children were more hospitalized for COVID‐19 infections compared to pandemic influenza. In addition, regardless of the type of pandemic infection, the underlying disease is an important factor for pediatric intensive care unit admission. This finding is important for developing strategies for the protection of children with the underlying disease in the upcoming pandemics. Highlights: The age was significantly higher in the COVID‐19 patients' group compared to the pandemic influenza group. The rate of underlying disease was significantly higher in the patients with H1N1pdm09 virus infections. The prevalence of underlying disease in patients requiring intensive care unit hospitalization was significantly higher compared to patients who did not require intensive care unit hospitalization regardless of COVID‐19 or H1N1pdm09 virus.